Lesion on palate: A diagnostic dilemma - Swati N Chavan; Jitendra K Rathod (Journal of Indian Academy of Oral Medicine and Radiology, 2016)
A non-ulcerated mucosal swelling on hard palate presents a challenge to the clinicians. Thorough clinical, radiographic and histopathological evaluations are mandatory. Here, we report a case of mucosal swelling on the hard palate of a 52-year-old male patient. On clinical examination, there was a dome-shaped, firm swelling seen on the left side of the posterior hard palate. On computed tomography (CT), the lesion appeared as round homogenously enhancing mass/lesion epicentered over the mucosa overlying the posterior part of the half of hard palate extending into the adjacent soft palate. When biopsy was performed, the histopathology report was suggestive of pleomorphic adenoma of palate. Pleomorphic adenoma is the most common tumor of the salivary glands; it accounts for approximately 60% of all salivary gland tumors. CT or magnetic resonance imaging should be considered when assessing for the presence of bony erosion or soft tissue and nerve involvement. Ultimately, complete surgical excision provides the definitive diagnosis and treatment for this noteworthy salivary gland neoplasm. Pleomorphic adenoma is commonly encountered in the parotid gland and other major salivary glands. At times they can also develop in minor salivary glands of the palate.